2021
DOI: 10.1111/camh.12514
|View full text |Cite
|
Sign up to set email alerts
|

Review: Ecological awareness, anxiety, and actions among youth and their parents – a qualitative study of newspaper narratives

Abstract: Background: Despite the growing impact of climate change on mental health, there have been few studies to date investigating how children and teenagers manage their ecological grief and eco-anxiety and how they can leverage it into environmental action. In this scoping review, we analyze lay press narratives about how youth respond to climate change to examine the dynamics between minors and adults around the evolving climate crisis. Methods: We included articles published between 2018 and 2021 in six of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 13 publications
0
73
1
2
Order By: Relevance
“…In our previous study of U.S. newspaper discourses surrounding young people and climate change, we observed one narrative that cast young people as emboldened activists, claiming and wielding power (5). In the present study, even if some participants described feelings of empowerment through engaging in climate action, these sentiments were far outweighed by expressions of powerlessness.…”
Section: Challenging News Media Narrativescontrasting
confidence: 50%
“…In our previous study of U.S. newspaper discourses surrounding young people and climate change, we observed one narrative that cast young people as emboldened activists, claiming and wielding power (5). In the present study, even if some participants described feelings of empowerment through engaging in climate action, these sentiments were far outweighed by expressions of powerlessness.…”
Section: Challenging News Media Narrativescontrasting
confidence: 50%
“…CCA has received growing attention in the popular press (Benoit et al, 2022 ), yet little research has examined how it relates to psychiatric symptoms, including symptoms of MDD and GAD. Furthermore, with more people, especially young people, taking action to address climate change, research is needed to explore how engaging in action may relate to both CCA and mental health symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Reimer (2013) argued that young adults are the ideal target for engaging in environmental activism because of their developmental stage, environmental knowledge, and ability to be effective messengers. At the same time, young people’s activism can also be stigmatized; for example, newspapers in the United States discussing climate change depict youth alternately as demanding activists, adultified kids, innocent victims, or ultimate saviors (Benoit et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that anxiety is characterized by intergenerational transmission, and in the family environment, the more obvious the anxiety of parents, the more likely children are to develop anxiety tendencies. 39 At the same time, the most direct response to parental education anxiety is to increase the child’s learning intensity, reduce the child’s entertainment and leisure time, and prematurely and over-develop the child’s cognitive ability. In this way, under the dual pressure of spirit and academics, children are prone to boredom and fear of learning, and parents treat their children with excessive intervention and control, which can easily cause their children’s test anxiety.…”
Section: Advance Research and Theoretical Assumptionsmentioning
confidence: 99%